Proses Pengambilan Keputusan dalam Perspektif Ibn Taimiyyah - Shobahussurur Shobahussurur (TSAQAFAH, 2010)
An important problem in the discourse of Islamic political study is the problem of decision-making process within the political order of a country. Does Islam follow a view of absolutism in the decision making process. How does representative institutions decision become a constitutional decision. What is the form of consultation can be done to get the best decision. Almost all forms of Islamic political thought agree to make syûrâ (consultation system, consulting) as a tool to create a state decision. Yet, the debate is on the problems that can be decided or determined through the mechanism of the syûrâ. For Ibn Taymiyyah, people are the main owners of state power. Determination of choice for power players and the way of power are completely in the hands of the people. They are the owners of the leadership in general. They are entitled to elect and dismiss the leader, as they also decide the broad outlines of state policy that must be done by him. Moreover, the authority outlines is not on the leader, but on the whole people. However, the syûrâ is not like the promoted Western liberal democracy. It has its characteristics, traits and principles.